A REVIEW OF COMMUNICATION TECHNOLOGIES FOR NEXT-GENERATION IOT WITH FOCUS ON 5G, LPWAN AND EDGE NETWORKING PARADIGMS - Singh, Mr. Ram Pratap (Journal of Global Research in Mathematical Archives(JGRMA), 2025)
This fast rate of digitalization, the device growth as they are connected, and the changing nature of how they are used are changing the nature of next-generation IoT systems. Flawless communication and low latency, combined with dependable connections, have emerged as essential prerequisites for smart IoT services in various fields, including remote monitoring, healthcare, industrial automation, and smart cities. At the forefront of this shift are the new communication technologies 5G, edge computing, and Low-Power Wide Area Networks (LPWAN). Regarding data speed, energy consumption, wide-area coverage, and real-time responsiveness, each offers special advantages. This paper presents a systematic survey of these enabling technologies, with an emphasis on their synergistic combination and complementary nature in providing scalable and survivable IoT infrastructures. The analysis identifies the factors through which the combination of 5G, LPWAN, and edge networking can address major issues in IoT rollouts, such as network overload, device heterogeneity, and the provision of distributed real-time analytics. Furthermore, the paper highlights some of the most significant implementation issues, including spectrum allocation, power limitations, security loopholes, and the lack of standardization. Through this review, an in-depth overview of the communication systems that will fuel the next generation of IoT is provided, with references made to existing capabilities, integration approaches, and research directions. Future research directions include the creation of harmonized architectures, secure-by-design communication models, and adaptive management of heterogeneous and dynamic IoT environments.